Carpathian Forests: Past and Recent Developments - (:unkn) unknown (Forests, 2024)
Forests of the Carpathians are of increasing research interest, as they cover a large area (>9 Mha) within European forests and are influenced by diverse environmental conditions and contrasting historical developments. We reviewed 251 papers dealing with Carpathian forests, their history, and future perspectives. Over 70% of articles and reviews appeared in the last ten years, and 80% refer to the Western and Eastern Carpathians, while the Serbian Carpathians remain a gap in this research field. Forest expansion and species changes have occurred since Holocene deglaciation, influenced by timber use, settlements, cropland development, and, since the Bronze Age, pasture activities. At higher elevations, early conifer successors have been increasingly replaced by Norway spruce (Picea abies), silver fir (Abies alba), European beech (Fagus sylvatica), and hornbeam (Carpinus betulus), while oaks have been present in the Carpathian foothills throughout the whole of history. In the 19th and 20th centuries, Norway spruce afforestation was favored, and timber use peaked. Recent transitions from agriculture to forest land use have led to a further increase in forest cover (+1 to +14% in different countries), though past forest management practices and recent environmental changes have impaired forest vitality in many regions; climate warming already causes shifts in treelines and species distributions, and it triggers pest outbreaks and diseases and affects tree–water relations. The risk of forest damage is the highest in monodominant Norway spruce forests, which often experience dieback after cascade disturbances. European beech forests are more resilient unless affected by summer droughts. In the future, increasing dominance of broadleaves within Carpathian forests and forest management based on a mix of intensive management and ecological silviculture are expected. Maintenance and promotion of silver fir and mixed European beech forests should be encouraged with respect to forest stability, biodiversity, and economic sustainability. As supported by the Carpathian Convention and related institutions and initiatives, connectivity, management, and stakeholder cooperation across administrative borders will be crucial for the future adaptive potential of Carpathian forests.
Keywords: mountain forests; climate change effects; sustainable forest management; mixed forests; tree species; literature review